2020
DOI: 10.1111/jocs.15233
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative resuscitation with hypertonic saline or hyperoncotic albumin in patients following cardiac surgery: A review of the literature

Abstract: Background Over‐resuscitation in postcardiac surgery patients is associated with significant morbidity and mortality. Accordingly, there is a growing interest in hyperoncotic albumin and hypertonic saline for resuscitation in patients following cardiac surgery. In this article, we will review the use of hyperosmolar fluid therapies for resuscitation in postcardiac surgical patients from the current literature. Methods A literature search was conducted in MEDLINE (PubMed) utilizing keywords, narrowing publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Therefore, overresuscitation is relatively common in patients under-going cardiac surgery. [19,53] Recent studies have shown that volume overload is independently associated with an increased risk of morbidity (e. g., pulmonary edema, AKI, and congestive heart failure) and mortality in patients who undergo cardiac surgery. [54][55][56] As a colloid, HSA is believed to remain in the intravascular space for a more extended period and thus provide intravascular volume expansion more efficiently than crystalloids.…”
Section: Hsa and Coagulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, overresuscitation is relatively common in patients under-going cardiac surgery. [19,53] Recent studies have shown that volume overload is independently associated with an increased risk of morbidity (e. g., pulmonary edema, AKI, and congestive heart failure) and mortality in patients who undergo cardiac surgery. [54][55][56] As a colloid, HSA is believed to remain in the intravascular space for a more extended period and thus provide intravascular volume expansion more efficiently than crystalloids.…”
Section: Hsa and Coagulationmentioning
confidence: 99%
“…[63] In addition, HSA is also believed to help recovery of the endothelial glycocalyx, [20] which creates an osmotic gradient that promotes interstitial fluid to shift from the extravascular space to the intravascular space. [19,64,65] However, adding HSA to diuresis does not appear to help with the diuretic effect. [65,66] Notably, postoperative interstitial salt and water overload are usually more evident in high-risk patients with impaired heart function, a long pump run, or a complicated procedure.…”
Section: Hsa and Coagulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of investigations for balanced versus normal saline crystalloid use come from mixed ICU populations, making their application to CT-ICU problematic [ 86 , 87 ]. Moreover, the use of albumin in continues to be controversial, with a mixed bag of results [ 88 ]. To date, the most significant positive results on prevention come from PrevAKI trials, where adherence to the Kidney Disease: Improving Global Outcomes (KDIGO) bundle reduced the rate of CSA-AKI in a single center RTC, and rate of moderate and severe AKI in a multicenter trial; the bundle consisted of avoidance of nephrotoxins, optimization of glycemic control, and optimization of volume status and hemodynamics [ 89 , 90 ].…”
Section: Part 2 – Selected Gaps In Knowledge and Future Direction Of ...mentioning
confidence: 99%